Development of higher education final judgment management information system using user-centered design method - Didi Supriyadi; Khairun Nisa Meiah Ngafidin; Jerry Lasama; Rafian Ramadhani (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
Final Judgment is a process of consideration to declare a student has met the academic and administrative requirements to hold a scholarship academic degree from the college. The Final Judgment management process business in universities involves many processes and stakeholders. Based on the result of observations and interviews, it is known that Final Judgment Management at the Informatics Faculty of ITTP is currently done manually by filling out the registration form and takes a long time for its processing. This study aims to develop Information Systems using User-Centered Design (UCD) methods that can meet the users' needs in implementing and managing Final Judgment processes. The developed system was tested for usability using a questionnaire to users with the Nielsen Attribute Usability (NAU) method. The method consists of five criteria, they are Learnability, Memorability, Efficiency, Errors, and Satisfaction. Usability test results showed: Learnability rate of 3.60, Memorability of 3.35, Efficiency of 3.90, Errors of 3.12, and Satisfaction of 3.63. Therefore, the average usability level of the Final Judgment system is 3.52. The user agrees that the developed Final Judgment information system has met the expected functional needs and is considered more effective and efficient.